The Relationship between Tyr113His Epoxidized Hydrolase Enzyme Gene Polymorphisms and the Incidence of Smoking Lung Cancer - Lucia Aktalina; Amira Permatasari Tarigan; Noni Novisari Soeroso; Yahwardiah Siregar; Ozar Sanuddin (Jurnal Respirologi Indonesia, 2018)
Background: This study aims to determine the relationship between the gene polymorphism of the enzyme Epoxid Hydrolase (EPHX) Tyr113His and the tendency of smokers to suffer from lung cancer. The EPHX Tyr113His gene polymorphism is a change in one nucleotide base of the EPHX gene to produce enzymes with decreased function by 50%. EPHX plays a role in the metabolism of chemical compounds in cigarette smoke, especially Benzo (a) Pyren (BaP), which becomes a carcinogen in the body. Methods: This study is a case-control study design conducted from October 2016 to February 2017. Venous blood was taken from 35 people with lung cancer at RSUP H Adam Malik Medan and 35 healthy smokers. The genotype examination of the EPHX gene was carried out using the PCR-RFLP method in the USU FK Integrated Laboratory. Results: The genotype frequency of heterozygous variant T/C and homozygous variant C/C in case groups was 83.3% and 16.7%, respectively. The frequency of the T allele in the case group was 41.67% and the C allele was 58.33%. Whereas in the control, the frequency was heterozygous variant T/C (80%) and homozygous variant C/C (20%). The frequency of the T allele in the control group was 40% and the C allele was 60%. There were no homozygous wildtype T/T genotypes in the two groups. There was no significant difference in the genetic distribution and allele distribution of the EPHX enzyme between case and control groups. Conclusion: There is no relationship between EPHX Tyr113His enzyme gene polymorphisms and the incidence of lung cancer in smoking. J Respir Indo 2018; 38(2): 93-9)